Erosion corrosion failure analysis of the elbow in sour water stripper overhead condensing reflux system. (April 2016) - Zhu, Min; Sun, Li; Ou, Guofu; Wang, Kai; Wang, Kuanxin; Sun, Yanlin
Abstract: The erosion corrosion failure of elbow of one oil refinery was investigated by using Aspen software, CFD technology and experiments. And the gas–liquid equilibrium distribution of H2 S and NH3 and multiphase flow simulation in the overhead system of a sour water stripper were obtained. The result shows that the component mole fraction of H2 S and NH3 rises markedly with decreasing temperature. At the outlet of air cooler, the temperature drops to 85 °C to form high concentration of ammonium bisulfide (NH4 HS), which would cause serious erosion corrosion at a certain flow rate and reveals an inhomogeneous thinning. The liquid phase fraction mainly distributes on the outside part of elbow, the more sour water accumulates there resulting in localized corrosion thinning. Meanwhile, the experiments show that when the concentration of NH4 HS reaches 10 wt.%, the corrosion rates increase rapidly with increased velocity. Thus controlling the concentration of NH4 HS below 10 wt.% in reflux drum would reduce the risk of erosion corrosion failure. Highlights: Failure is caused by erosion corrosion in higher liquid phase fraction local region. Corrosion rates increase rapidly with increased NH4 HS concentration and velocity. The comprehensive failure analyses agree well with reality.